Students' Satisfaction Towards the Use of E-learning during the Global Pandemic - Daisy Mui Hung Kee; Aina Dayana Fozeli; Norarnitasha Abdullah Sani; Ainin Sofiya Mustafa; Nur Afifah Khalid; Pooja Chawla; Varsha Ganatra (Asia Pacific Journal of Management and Education (APJME), 2021)
During the global pandemic, e-learning became even more popular and used by many educational institutions worldwide to facilitate the students' learning process. Students can easily get the related materials and resources from e-learning. This research intends to examine the level of students’ satisfaction with e-learning and their learning experiences during the global pandemic. The quantitative research method was carried out using a questionnaire survey and online research. A total of 150 students from different institutions in India and Malaysia have participated in the survey. The survey was carried out through Google Form and the data were exported to be analyzed using SPSS. The results showed that most of the students were satisfied with e-learning and how it helped them in their studies. The results of this study indicated that convenience flexibility was significantly related to students’ learning experiences.